Pencitraan Lahan Kelapa Sawit Menggunakan Unmanned Aerial Vehicle - Alfaridho Haqiqi; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
According to the Central Statistics Agency (BPS), in 2020, palm oil is the first commodity in Riau Province. Until 2020, the total area of oil palm land in Riau province reached 2,424,545 hectares. As a leading commodity, it is necessary to monitor land accurately and periodically to control the productivity of oil palm land Unmanned aerial photography technology or commonly called Unmanned Aerial Vehicle (UAV) can support spatial data providers on a fairly large scale. In addition to being effective and efficient both in terms of cost and time of use, UAVs can also produce fairly clear photos. The mapping process can also be done automatically with aerial photo processing software. This research was conducted in Kandis District on land owned by Mr. Legimin with an area of 30 hectares using a SkyWalker fixed wing UAV. The steps used in this research are drone preparation, flight altitude planning, drone testing on the ground, camera calibration settings, taking aerial photos, viewing aerial photos, then analyzing aerial photos. Aerial photos are combined to form a mosaic of upright photo images, namely Orthophoto which is the basis for making a fairly accurate map of oil palm land.Keywords: Palm Oil, Aerial Photos, UAV